CURRÍCULO, GÊNERO E EDUCAÇÃO: IMPLICAÇÕES DAS LEGISLAÇÕES NAS INSTITUIÇÕES DE ENSINO DO ESTADO DE MATO GROSSO DO SUL - GUSTAVO FRANCO DE QUEIROZ GONZALEZ (2023)
The approach to gender identity and diversity has been widely discussed in different areas of knowledge, but in education it has more significant implications. In addition, analyzing legislation and documents, whether at the national or local level, helps to strengthen which perspectives are included or excluded from educational curricula. By identifying the curricula through history, a clear distinction can be seen with regard to gender issues and, from there, a series of behaviors that are evidenced in educational practice can be ascertained. In this way, this research seeks to highlight approaches to gender identity and diversity through curricula and legislation, identify their implications and what may or may not be portrayed today, based on a bibliographical analysis and official documents. For the development of this study, the foundations of legislation that address the issue of gender identity and diversity in Brazil and Mato Grosso do Sul were used. The research developed in this work will be through a qualitative methodology that is the path of thought and the practice exercised in the approach of reality and that includes the theoretical conceptions of the approach, the set of techniques that make possible the construction of reality, of the creative potential of the investigator. In view of what has been exposed, based on a bibliographical and documental research, this study intends to elaborate an ordering of the collected data, so that, later, the actual analyzes of the collected material can be carried out, thus allowing a critical reflection between the approach theory and the researched object. Keywords: Gender diversity. Curriculum. Legislation. Education.